2021
DOI: 10.3390/cells10112985
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cytokine Mix-, Imiquimod-, and Serum-Induced Monoculture and Lipopolysaccharide- and Interferon Gamma-Treated Co-Culture to Establish In Vitro Psoriasis-like Inflammation Models

Abstract: Psoriasis (Ps), commonly perceived as a skin and joint disorder, has a complex basis and results from disturbances in the sophisticated network between skin and the immune system. This makes it difficult to properly depict the complete pathomechanism on an in vitro scale. Deciphering the complicated or even subtle modulation of intra- and intercellular factors, assisted by the implementation of in vitro human skin models, may provide the opportunity to dissect the disease background step by step. In addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…These include the model based on the concurrent stimulation of the HaCaT culture with IL-17A, IL-22, oncostatin-M, IL-1α, and TNF-α [7]. This M5 stimulation model mimics typical features of psoriasis, including pro-inflammatory response and keratinocyte hyperproliferation, accompanied by inhibition of keratinocyte differentiation and increased expression of psoriasis-related biomarkers [21]. This model was implemented and characterized an elevated inflammatory response, evaluated by an increase in IL-6 and IL-8 production, augmentation of S100A7, S100A9, CXCL1, and CCL20 expression, and an increase in the proliferation in HaCaT cells, consistent with the psoriasis-like phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the model based on the concurrent stimulation of the HaCaT culture with IL-17A, IL-22, oncostatin-M, IL-1α, and TNF-α [7]. This M5 stimulation model mimics typical features of psoriasis, including pro-inflammatory response and keratinocyte hyperproliferation, accompanied by inhibition of keratinocyte differentiation and increased expression of psoriasis-related biomarkers [21]. This model was implemented and characterized an elevated inflammatory response, evaluated by an increase in IL-6 and IL-8 production, augmentation of S100A7, S100A9, CXCL1, and CCL20 expression, and an increase in the proliferation in HaCaT cells, consistent with the psoriasis-like phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of several psoriatic biomarkers, including S100A7 and S100A9, has been identified and shown to be induced in the M5 stimulation model [21]. For example, S100A7 (psoriasin) is an antimicrobial peptide, which also limits keratinocyte differentiation and induces their proliferation, mainly through IL-6 induction [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…These KTs can come from primary cultures or from immortalized lines. Immortalized KT lines include HaCaT cells [24,[44][45][46][47] and N/TERT1, N/TERT2G [48]. Coculture monolayer consists of coculture of KTs with immune cells.…”
Section: D Modelsmentioning
confidence: 99%
“…Coculture monolayer consists of coculture of KTs with immune cells. One example of this is the coculture of HaCaT cells with human leukemia monocytic cell line (THP-1) [44]. These KT-T cell coculture systems suggested that KT-T cell communication can recruit immune cells into the skin by secreting chemokines as well as regulating T-cell differentiation [49].…”
Section: D Modelsmentioning
confidence: 99%
See 1 more Smart Citation